Study on the Path of Combining Chinese Teaching as a Foreign Language and Tea Culture in Indonesia During the Post-Epidemic Period - Li, Longyu (Mandarinable: Journal of Chinese Studies, 2000)
In the post-epidemic period, cultural teaching is still an important part of the process of teaching Chinese as a foreign language, as well as it is the starting point for communication and cooperation between countries and cultures. This paper discusses the current situation of the development of tea culture in China and Indonesia and explores the realization path of tea culture exchange in teaching Chinese as a foreign language and the idea of combining tea culture in teaching design.